(untitled) (Philological Studies, 2019)
The Russian Historical, Geographical, Political and Civil Dictionary,’ compiled by Vasily N. Tatischev in 1744–1746, was the first Russian encyclopaedia. Various thematic groups of the vocabulary and geographical names of Russia and other countries are described in the Dictionary. Tatischev characterized many toponyms of the Urals area, such as names of rivers Аять (Ayat’), Белая (Belaya), Вишера (Vishera), Ирень (Iryen’), Кама (Kama), names of places Великая Пермь (Velikaya Perm’), Веретья (Veretya), Верхотурье (Verkhoturye), Екатеринбург (Yekaterinbourg), mountains and mountain ridges Великий Пояс (Velikiy Poyas), Благодать (Blagodat’), Говорливая гора (Govorlivaya gora), and others. He has developed the structure of the toponymic entry, which includes the following components: the head word, the reference to the named object (a river, a mountain, a town) and its geographical characteristics, the etymology of the toponym (if available), its linguistic characteristics and its translation, as well as historical and ethnographical materials which characterize the corresponding object.